MENINGKATKAN KEMAMPUAN ESTIMASI ROUNDING TERHADAP PENJUMLAHAN MELALUI PEMBELAJARAN BERBANTUAN KARTU DAN GARIS BILANGAN PADA SISWA KELAS VB SDN 2 TAMAN SARI LOBAR - Yuni Maryati Yuni Maryati (Ibtida'iy : Jurnal Prodi PGMI, 2017)
The study was conducted to examine the improving ability of the estimation rounding of the students through assisted card learning and number line to describe the application of assisted learning and the number lines that improve the students rounding estimation’s ability of VB class of 2 Taman Sari State Elementary School, West Lombok.This study used classroom action research. In this case, the researcher had a role as a conduit of action, a key instrument, a reporter of the research results, and an interviewer on the research subjects. The data of this study are in the form of the review of the student test answers and the interviews. The data was collected by researcher by using the student activity observation sheets, field notes, teacher observation sheets, guidelines for scoring test questions, and interviewing guides. The Result of the study shows thatthe application ofassisted card learningandthe number line which canimprove the ability of rounding estimationconsistsof5stages namely:(1) observingthe card and number line, (2) writing down the reasons of estimation in the card,(3) displaying card whichcontainsthe estimation resultan,(4) comparing the estimationrounding,(5) presenting thereasonswiththe card. The criteria of  success which was specified by the researcher had been achieved in the second cycle. More detail the percentage of the students who did not make the mistake of the concepts, the calculations, and the procedures was as follows: (1) the percentage of the students who did not make the mistake of the concept was 76%, (2) the percentage of the students who did not make the mistake of the procedures was 70%, and (3) the percentage of the students who did not make the mistake of the calculation was 94% and (4) the percentage of the students who had reached the KKM was 87%.